Socialization and Practice of Ice Breaking Anti Boring at SMAN 11 Sinjai - Inar Inar; Salam Salam; Irmayanti Irmayanti (Yayasan Adra Karima Hubbi, 2024)
Background. Ice breaking is one way that can be done by the teacher so that the students do not feel bored, bored and sleepy in the full day school learning process. Teachers at SMAN 11 Sinjai have implemented ice breaking, but it's still monotonous. Purpose. The purpose of this community service activity is to inform as well as implement various kinds of ice breaking to the teachers of SMAN 11 Sinjai. Method. The method used in community service is socialization and practice. The subject of dedication is a teacher at SMAN 11 Sinjai. The implementation stages are preparation, implementation and reflection. Preparation which includes outreach to school principals and teachers and agreeing on a schedule for implementing community service. The implementation, namely the accompanying team carried out socialization, presentation and practice of ice breaking. While reflection is giving feedback to training participants and participants filling out questionnaires related to community service activities. Results. The result of this community service is that teachers can master and implement various kinds of ice breaking, especially for their students in the learning process in implementing the full day school. Conclusion. The application of ice breaker looks easy but requires sufficient skill, creativity and training so that the teacher is able to integrate it into the learning atmosphere in the classroom. This is caused without adequate knowledge so that learning using ice breaker becomes more noisy and meaningless.